PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANITA ISLAM ( YKWI ) PERANAN YAYASAN KESATUAN WANIT - sari, Devi Wanda; ', Marwoto; ', Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The role is a One thing that became the principal cause or a major influence in the occurrence of an event. Education became one of the problems faced by Indonesia until now and therefore was YKWI Initiating and open educational activities for perempuan.Sampai now YKWI still standing despite his already not as much as before anymore, it is because there are many schools in the city pekanbaru. The condition of women in Malay culture, including in Riau, the first third of the 20th century filled with social problems associated with such traditional enclosed or seclusion of girls. Marital problems are also emerging, such as child marriage, forced marriage, elopement, polygamy, and divorce. Contemporary literary works of Riau, like Love Ta 'Concentrated (1931) and for Thieves Son of the Virgin (1932) Hs Soeman work also implies a story about women and tradition. Pros and cons of education for women was also widely reported in the local newspaper published in Padang, Medan, and Batavia. This condition is commonly experienced by women in Indonesia in various places, so that later on the agenda in the Indonesian Women's Congress (1928) in Yogyakarta and the Congress of Indonesian Female Engagement (1929) in Jakarta. This study aims to determine the background of women's education in the city YKWI pekanbaru, to find out who is struggling to realize the education of women in the city of Pekanbaru, to know the history of the YKWI in Pekanbaru city, to determine the role of education YKWI against women in the city of Pekanbaru, as well as the development YKWI The city of Pekanbaru hitherto The theory is used to analyze this problem is Sosial.Metode movement theory used is the historical empirical method using in-depth interview and direct observation to the study site. Based on the results of research in the field it can be concluded that the original YKWI an association number of mothers in pekanbaru who hold religious social activities, especially education for women and children under the leadership of John Syamsidar. From interviews wird for their routine for the mothers also always held every Friday and until now is still performed recitals wird.Keywords: Role, YKWI, Education, Women, Pekanbaru.